The Effect Locus of Control and Need for Achievement Towards Entrepreneurial Performance - Rayawan, W.; Efrata, T. C. (Review of Management and Entrepreneurship, 2017)
Entrepreneurs are the key generator of economic growth. In this research, the characteristics of the entrepreneurs are being evaluated. Particularly, the locus of control and the need for achievement are being examined to find out their impact towards the entrepreneurial performance of the entrepreneurs. 50 young entrepreneurs are being selected as the research samples using random sampling.The result shows that both the locus of control and need for achievement have a significant effect towards their entrepreneurial performance. The benefit of this research is to provide entrepreneurs with a different perception of what actually contributes to the characteristics of them. The research is conducted within entrepreneurs so that we really know if it really affects them or not. And more importantly, we use sample of entrepreneurs who owns a business solely, as such their effect will be more influenced towards their business instead of multiple leadership or long organizational structure.